The protective effect of the intestinal microbiota in type-1 diabetes in NOD mice is limited to a time window in early life - Fernandez Trigo, Nerea; Kalbermatter, Cristina; Yilmaz, Bahtiyar; Ganal-Vonarburg, Stephanie C. (Frontiers in Endocrinology, 2024)
The incidence of type-1 diabetes (T1D) is on the rise, particularly in developed nations, and predominantly affects the youth. While genetic predisposition plays a substantial role, environmental factors, including alterations in the gut microbiota, are increasingly recognized as significant contributors to the disease. In this study, we utilized germ-free non-obese diabetic (NOD) mice to explore the effects of microbiota colonization during early life on T1D susceptibility. Our findings reveal that microbiota introduction at birth, rather than at weaning, significantly reduces the risk of T1D, indicating a crucial window for microbiota-mediated modulation of immune responses. This protective effect was independent of alterations in intestinal barrier function but correlated with testosterone levels in male mice. Additionally, early life colonization modulated T cell subset frequencies, particularly T helper cells and regulatory T cells, in the intestine, potentially shaping T1D predisposition. Our findings underscore the pivotal role of early-life microbial interactions in immune regulation and the development of autoimmune diseases.